KNOWLEDGE AND AWARENESS OF ARITHMOPHOBIA AMONG UNDERGRADUATE DENTAL STUDENTS IN CHENNAI - A QUESTIONNAIRE SURVEY - Neha R, Dhanraj Ganapathy, L. Keerthi Sasanka (Drugs and Cell Therapies in Hematology, 2022)
Background: The fear of numbers is called arithmophobia. It is also called numerophobia. Arithmophobia is usually rooted in superstition or religious phobias.it is an exaggerated, constant, and irrational fear of numbers that can affect one’s daily routine like Performing complex mathematical computations becomes a herculean task, with individuals stuttering and sloughing through the ups and downs of numbers. This also has origins from our childhood, often combined with a negative experience with number Arithmophobia. Aim: To assess the arithmophobia among dental students. Materials And Methods: Cross-sectional descriptive studies, employing the convenience sampling method were conducted to know whether there are people suffering from arithmophobia symptoms.In which 113 undergraduate students participated through an online survey. Data analysis was done in the SPSS software version 23. Descriptive statistics were used. Result: From this study, it can be concluded that nearly 32% of the population were aware of arithmophobia. Conclusion: Most people have experienced the fear of numbers at some stage of their life. This cross-sectional study explored the knowledge and awareness among dental students about arithmophobia, even though dentists don’t deal with numbers in studies but in day-to-day life, they are exposed to numbers. so that there is a little bit of fear among some people.